"Your friendly neighborhood heroines" a study of everyday life depiction in chick lit novels - Lampa, Karenina Isabel A.; Vitorio, Raymund Victor M. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2012)
This thesis looks at how everyday life is depicted in the chick lit novels and how this depiction is able to affect the readers. As chick lit continues to become popular genre in the present time, a study on it becomes beneficial to society. Chick lit is treated as a repository of everyday acts, and so one must take a look at whether this is an accurate treatment or not. The everyday that is portrayed in these novels are not a reflection of everyday life, but a refraction of it; the treatment of the chick lit novel as a mirror of the real everyday, then becomes problematic. Three chick lit novels, Bridget Jones' Diary, Confessions of A Shopaholic, and Watermelon were analyzed separately, focusing on how these novels depict everyday life for their heroines. It examined the heroine's persona, her family, her friends and colleagues, and finally her lover. The heroine then was placed in the setting of the everyday life in relation to all these. After the three novels were analyzed separately, a synthesis was made which looked at the similarities of everyday life that were present in the novels. The conclusion that was arrived at states while chick literature contains some elements of the real everyday life, its portrayal in these novels somehow "distorts" the everyday. It is a refraction of everyday life - which means that some elements of the reality are taken and shaped into something else. And while this refraction becomes a way of celebrating what would have been the mundane, repetitive acts of everyday life, it also poses a problem as it can make certain aspects of everyday life that used to be special, turn to something trivial.
Thesis (B.A. in English Studies : Anglo-American Literature)--University of the Philippines Diliman
Includes bibliographical references and appendices.